TEKANAN WAKTU AUDIT DAN DUE PROFESIONAL CARE TERHADAP KUALITAS AUDIT (Jurnal Riset Akuntansi, 2023)
In each audit activity, the auditor often encounters obstacles in managing the audit process time which is very short compared to the stages that must be carried out in the audit process. The time pressure of a very tight audit process can affect a decrease in audit quality. There are still public accountants who misjudge the accounts in the financial statements. In this case, this research is more on the study of grounded theory which emphasizes the efforts of researchers in conducting an abstract analysis of a phenomenon, with the hope that this analysis can prove certain theories that can explain phenomena specifically. As for the problems regarding the quality of audits that occur in Indonesia in general and audits in the city of Bandung. The results of this study provide empirical evidence that the higher the audit time pressure, the lower the quality of audit results and conversely the lower the audit time pressure will improve audit quality. The results of this study provide empirical evidence that the higher the due professional care, the higher the quality of the audit results.